2014
DOI: 10.1002/jrs.4626
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy as a tool to the in situ study of three lichens species from Antarctica and Brazil

Abstract: In this investigation the chemistry of the lichens Gondwania regalis, Teloschistes exilis and Xanthoria candelaria (Teloschistaceae) have been recorded by means of Raman spectroscopy. The non‐destructive analysis provided the recognition of parietin and conjugated polyenes, probably belonging to the carotenoid family for all the investigated specimens. Bands at ca. 1370 and 1600 cm−1, respectively, assigned to the ν(C―O) and ν(CO) modes of the phenyl group of the anthraquinone compound, as well the bands at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…To differentiate between the blue to red gloeocapsin pigment and the yellow-brown scytonemin pigment, Raman spectra of Hyella balani, which are known to contain *Vibrational assignment following Edwards et al, 1999Edwards et al, , 2003Edwards et al, , 2005bParab and Tomar, 2012;Jehli cka et al, 2014;Fernandes et al, 2015. m: stretching; d: in-plane bending; q:…”
Section: Raman and Photospectrometry Characterizationmentioning
confidence: 99%
“…To differentiate between the blue to red gloeocapsin pigment and the yellow-brown scytonemin pigment, Raman spectra of Hyella balani, which are known to contain *Vibrational assignment following Edwards et al, 1999Edwards et al, , 2003Edwards et al, , 2005bParab and Tomar, 2012;Jehli cka et al, 2014;Fernandes et al, 2015. m: stretching; d: in-plane bending; q:…”
Section: Raman and Photospectrometry Characterizationmentioning
confidence: 99%
“…Figure 3 shows the Raman spectrum of X. parietina in which four of these characteristic parietin bands have been identified. Three other features in this spectrum can be assigned to a carotenoid with bands at 1527, 1154 and 1003 cm −1 , these being the C = C, C-C and C = CH modes, respectively, of the unsaturated carotenoid chain (Fernandes et al 2015; Withnall et al 2003). The band assignments are given in Table 1; from the position of the C = C stretching band it is possible to identify the carotenoid as zeaxanthin.…”
Section: Resultsmentioning
confidence: 99%
“…[45] Fernandes et al used Raman spectroscopy as a tool to the in situ study of three lichens species from Antarctica and Brazil, They found that the non-destructive analysis provided the recognition of parietin and conjugated polyenes, probably belonging to the carotenoid family for all the investigated specimens. [46] Fraser and co-workers have carried out a Raman spectroscopic study of teeth affected with molar-incisor hypomineralisation. Principal component analysis highlighted changes in the phosphate structure and variations in various organic constituents.…”
Section: Cells Bacteria and Virusesmentioning
confidence: 99%